Chemical and enzymatic synthesis of the alginate sugar nucleotide building block: GDP-d-mannuronic acid. (1st November 2019) - Beswick, Laura; Ahmadipour, Sanaz; Dolan, Jonathan P.; Rejzek, Martin; Field, Robert A.; Miller, Gavin J.
Graphical abstract: Image 1 Highlights: Sugarnucleotide synthesis. Chemical and enzymatic access to GDP-d -ManA. Evaluation of protected and free uronate 1-phosphates for pyrophosphorylation.